Empresariado e política no Brasil contemporâneo: o discurso da FIESP e dos banqueiros frente à política econômica do governo Dilma Rousseff (2011-2014) - Vaccari, Gabriel da Silva (2016)
This dissertation has as its theme the relationship of business elites of the financial sector and industry with the state economic policy in contemporary Brazil. Our object of the research, in precise terms, the discourse of the Industries Federation of São Paulo State (FIESP) and the bankers about the government's economic policy Dilma Rousseff (PT), in 2011-2014. Our sources of access to the object are i) articles, interviews and written statements / granted by industry business leaders and finance, published in the mainstream press organs; ii) materials and news (also from the press) about facts that were the contexts and the political situation analyzed here; iii) public notes and documents offered by FIESP and the Brazilian Federation of Banks (Febraban). The objective of this work is to identify, analyze, understand and compare i) ideological profiles and ii) the political positions - related to economic policy dilmista -, that can be inferred from the discursive productions of FIESP and bankers. Our main finding is that, even with ideological profiles, schedules and distinct modes of public behavior among themselves, after Dilma has implemented in his first presidential term economic policy matrix that significantly strengthened the role of State intervention in the Brazilian economy - the neodevelopmentalist offensive - both bankers as industrial submitted ratings and positions fairly critical of the economic model of government. Thus, the period analyzed here would have been marked by political tension of relations between industrial and financial business community with the federal government.